Morphodynamic Response of Estuaries to Climate Change - Yunzhu Yin (2018)
Estuaries are one of the most important aspects of coastal systems globally. They are often hubs for human civilisation due to the socioeconomic advantages they offer. As they are highly vulnerable to natural forces, including tides, waves, surges and river discharges, it is essential to study the relationship between estuarine morphologies and these natural variables, which is crucial in order to assess estuarine evolution.The Deben Estuary (UK) has been selected as the case study in this study as its morphology has been significantly changed over time. It can be expected that the estuary will undergo significant morphodynamic changes under future climate change. The objective of this study is to investigate the morphodynamic responses of the estuary to the climate change in order to better understand the relationship between morphological change and climate change.A regional scale depth-averaged hydrodynamic and morphodynamic model Delft 3D was set up to the Deben Estuary, which incorporates wave propagation. The model was validated against measurements of water levels and waves before using it to simulate detailed scenarios. Then, the future climate projection data was used as the boundary conditions for the model scenarios. First, the calm weather conditions were considered since the model was run in long-term time scale. Then the episodic events were accounted for to investigate the impact of waves in future storms on the estuarine morphodynamics.The results show that future climate change will enforce different responses of morphodynamics at the estuary. Responses vary depending on whether natural forces are episodic or long term, and also according to different climate change scenarios, such as different emission scenarios. The comparison between the responses under the present and future conditions indicates that the estuary may undergo different evolution to what is historically observed.